THE ASSOCIATION BETWEEN MATERNAL FACTORS AND THE INCIDENCE OF LOW BIRTH WEIGHT IN WEST SUMATRA PROVINCE: AN ANALYSIS OF THE 2024 INDONESIAN NUTRITIONAL STATUS SURVEY DATA: LOW BIRTH WEIGHT - Zahira Maya Syofa; Vivi Triana; Kamal Kasra (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2026)
Background: Low Birth Weight is a major cause of infant mortality and serves as a key indicator for assessing a country's health status. This study aims to analyze the relationship between maternal factors and the incidence of Low Birth Weight in West Sumatra through an analysis of the 2024 Indonesian Nutritional Status Survey data. Methods: The study was conducted from August 2025 to March 2026 using a cross-sectional study design. A total sampling method was applied, resulting in a sample size of 5,834 infants. The analysis included univariate, bivariate, and multivariate analysis. Results: The prevalence of LBW in West Sumatra was 7.2%. Bivariate analysis revealed that hypertension (p=0.0001), intrauterine growth restriction (p=0.0001), and preeclampsia (p=0.0001) were significantly associated with LBW. In contrast, anemia, parity, excessive gestational weight gain, and ANC visits did not show significant relationships. Multivariate analysis identified intrauterine growth restriction as the most dominant risk factor (AOR=18.616), followed by preeclampsia (AOR=3.164) and hypertension (AOR=2.477). Conclusion: Intrauterine growth restriction, preeclampsia, and hypertension are the primary determinants of LBW incidence in West Sumatra. Strengthening the quality of medical risk screening and intensive fetal growth monitoring within antenatal care (ANC) services is urgently required as a preventive measure.